Victim Protection in Social Engineering Cybercrime: an Islamic Legal Perspective - Dendy Krisandi; Abdul Halim; Hardi Muhar Sungguh (International Journal of Law and Society, 2026)
This research examines Islamic legal protection for victims of social engineering crimes within the context of cybercrime. Social engineering is a form of digital crime that exploits psychological manipulation and trust to obtain personal data, system access, or financial benefits. Such crimes cause not only material losses but also immaterial harm, including psychological trauma, violations of privacy, dignity, and personal security. However, positive legal frameworks tend to prioritize offender punishment, while victim protection and recovery remain insufficiently addressed. This study adopts a qualitative approach with a normative-juridical research design, complemented by limited empirical insights. Data were collected through library research on Islamic legal sources—namely the Qur’an, Hadith, and fiqh jināyah—alongside statutory regulations on cybercrime and selected interviews with legal scholars and practitioners. The analysis employs a descriptive-analytical method grounded in the maqāṣid al-sharī‘ah framework, particularly the principles of ḥifẓ al-māl (protection of property), ḥifẓ al-‘irḍ (protection of dignity), and ḥifẓ al-nafs (protection of life and psychological security). The findings demonstrate that Islamic law provides a robust normative foundation for protecting victims of social engineering crimes. Such protection extends beyond retributive punishment through ta‘zīr and emphasizes restorative justice by prioritizing victims’ rights restoration, offender accountability, and public welfare. Islamic law is both adaptive and relevant in addressing contemporary cybercrime challenges and may serve as a humanistic, just, and responsive model for victim protection in the digital era.